The Effectiveness of Using Smartphones as Mobile-Mini Labs in Improving Students’ Beliefs in Physics - Tanti, Tanti; Deliza, Deliza; Hartina, Siti (STKIP Singkawang, 2024)
This study aims to determine the efficacy of using smartphones as portable mini-labs to improve students' beliefs about physics. This study takes a hybrid approach, using an exploratory mixed-method research design. The qualitative step entails creating teaching resources as a laboratory manual focusing on momentum and impulse. Simultaneously, the quantitative phase evaluates the usefulness of using smartphones as mobile mini laboratories to improve students' beliefs about physics and the process of learning physics using a quasi-experimental, non-equivalent control group design. According to the research findings, the laboratory manual developed during the qualitative stage has been declared valid and appropriate for learning by expert validators and teacher practitioners. Furthermore, using smartphones as portable tiny laboratories in physics teaching significantly improves students' beliefs about physics, notably the dimension of real-world connection, which has grown significantly. This research will have favourable implications for enhancing beliefs and proficiency in physics topics and cultivating students' interpersonal and communication abilities. Laboratory activities are crucial since they provide students the chance to partake in diverse genuine scientific procedures, including the design and execution of experiments, the gathering and analysis of data, and the dissemination of scientific knowledge.